IbM Kelompok Ternak Kelinci dan Kelompok Tani Cabai di Desa Mekarsari dan Sidorejo, Kecamatan Kabawetan, Kabupaten Kepahiang, Provinsi Bengkulu - Risvan Anwar; Eka Suzanna (Institut Pertanian Bogor, 2017)
IbM program for farmer group partners rabbits Tani Mulya village Mekarsari aims to provide knowledge and business skills make Bokashi fertilizer and liquid organic fertilizer by utilizing waste rabbits are widely available in the village Mekarsari as one of the productive economic activities. Program for partners Rational Kepahiang chili farmer groups is to give knowledge and skills in chili cultivation by utilizing Bokashi rabbit droppings and urine POC rabbits to substitute the use of inorganic fertilizers and pesticides, as well as increase production of chili plants. Methods of execution include: (1) Extension and technical guidance of making modifications to the enclosure; (2) Training and technical guidance manufacture Bokashi rabbit feces and urine POC (3) Extension and technical guidance packaging and manufacture of trademarks Bokashi rabbit feces and urine POC; and (4) Extension and demonstration plot curly chilli cultivation. The conclusion of this program are members of the group partner 1 (Tani Mulya) already know and understand in modifying enclosures so that the urine of rabbits can be disposed of easily, leftover food and feces collected well, where food is specially concentrate that is easily accessible rabbits and easy to clean, the food in the form of special herbs are easy to reach and a special drink that rabbit feels comfortable, environmental sanitation is better and easier to collect waste enclosure to be used as organic fertilizer. In addition, farmers' groups have been able to make fertilizer bokashi of solid waste and liquid waste rabbits, making the brand and market Bokashi manure they produce. Members of farmers group partner 2 (Rational Kepahiang) already know and understand the chilli cultivation by utilizing Bokashi rabbit droppings and urine POC rabbit in order to substitute the use of inorganic fertilizers and pesticides.